2022
DOI: 10.1021/acs.jafc.1c06939
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Changes in the Structure and IgE-Binding Ability of Ovalbumin Glycated by α-Dicarbonyl Compounds under Simulated Heating

Abstract: As a complex reaction, biological consequences of the Maillard reaction (MR) on dietary proteins need to be deciphered. Despite previous studies on the structural and antigenic properties of ovalbumin (OVA) by MR, associated changes induced by specific MR intermediates and their downstream products are largely unknown. This study focused on the impacts of glycation by α-dicarbonyl compounds (α-DCs), intermediates of MR and precursors of advanced glycation end-products (AGEs), on the structural and IgE-binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…[33,34] In our previous report, we demonstrated that glycation of OVA with typical AGE precursors like MGO and glyoxal could reduce the IgEbinding level of OVA by up to 72% when heating at 95 °C. [20] The locations of AGE-modified sites, as revealed by high-resolution mass spectrometry (MS), were found to fall within the sequences of several known epitopes of OVA, thus providing a masking effect on the epitope-sIgE recognition. However, it is worth noting that a lower IgE-binding ability does not guarantee hypoallergenicity in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[33,34] In our previous report, we demonstrated that glycation of OVA with typical AGE precursors like MGO and glyoxal could reduce the IgEbinding level of OVA by up to 72% when heating at 95 °C. [20] The locations of AGE-modified sites, as revealed by high-resolution mass spectrometry (MS), were found to fall within the sequences of several known epitopes of OVA, thus providing a masking effect on the epitope-sIgE recognition. However, it is worth noting that a lower IgE-binding ability does not guarantee hypoallergenicity in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Both diets were manufactured by Xietong Bioengineering Co., Ltd. (Nanjing, China), and as shown in Table S1, Supporting Information the two diets were free of allergen and identical in calories and macronutrients level. Generation of fluorescent AGEs in the OVA-AGE or H-AGE diet was determined by fluorometry as described by the previous report, [56] and the contents of 10 specific AGEs, namely, CML, CEL, MG-H1/3, MG-H2, G-H1, pyrraline, pentosidine, argpyrimidine, and MOLD were quantified by an isotope dilution-based UHPLC-MS/MS method as indicated by Zhang et al [20] In Vitro IgE-Binding Ability of OVA-AGE: The IgE-binding ability of OVA-AGE was analyzed by an indirect competitive ELISA assay according to the protocol reported elsewhere. [20] In brief, the OVA solution (0.5 mg mL −1 ) dissolved in 0.05 M carbonate buffer solution (pH 9.6) was coated on a 96-well plate (2 μg protein per well) and then kept overnight at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Maillard reaction is induced by reducing sugars, which could alter the structures and physicochemical properties of dietary proteins due to sugar degradation products. a-Dicarbonylic compounds (a-DCs) like glyoxal (GO) and methylglyoxal (MGO) are important intermediates of the Maillard reaction that exist during thermal processing ( Dasanayaka et al, 2022 , Gupta et al, 2018 , Zhang et al, 2022 ). In addition, the a-DCs also inevitably react with the shrimp protein as the shrimp reheats.…”
Section: Introductionmentioning
confidence: 99%